2021
DOI: 10.18488/journal.1.2021.115.240.249
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Mediational Process in Social Learning During Online Language Learning

Abstract: Online learning has become a new trend in the world. To teach online effectively, the instructors have to improvise their course content. Learners have mixed feelings over online learning, some of them prefer the face-to-face teaching; but some are comfortable with the online teaching mode. Previously, the success of language teaching has always depended on face-to-face interaction. However, language is taught online now. Therefore, this study was carried out to investigate the mediational process in social le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is important so learners can sustain their interest to complete the course. The study by Sukimin, et al (2021) also found that the online presence is needed to make sure learners do not drop out of the course. Figure 7 reveals the summary of mean scores for all type of online presence investigate in this study.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important so learners can sustain their interest to complete the course. The study by Sukimin, et al (2021) also found that the online presence is needed to make sure learners do not drop out of the course. Figure 7 reveals the summary of mean scores for all type of online presence investigate in this study.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 99%
“…Studies have also been done to show the role of technology in learning. The study by Sukimin, Rahmat, Mok, Arepin, Zainal Abidin, & Haron (2021) investigated the mediational process in online learning. 111 respondents who were diploma, bachelor degree and postgraduates participated in this quantitative study.…”
Section: Past Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sure enough, having to attend online classes is one level ahead for many learners who used to look at online interactions as non-academic. As such, the study by Sukimin, et al (2021) and Janssen & Wubbles (2016) suggested that future researchers look into group interactions among learners during online learning. It would be interesting to see how learners are coping with online group interactions.…”
Section: Background Of Studymentioning
confidence: 99%